Origins and pathogenesis of Middle East respiratory syndrome-associated coronavirus: recent advances - Goldstein, Stephen A. (F1000Res, 2017)
Middle East respiratory syndrome-associated coronavirus (MERS-CoV) has been a significant research focus since its discovery in 2012. Since 2012, 2,040 cases and 712 deaths have been recorded (as of August 11, 2017), representing a strikingly high case fatality rate of 36%. Over the last several years, MERS-CoV research has progressed in several parallel and complementary directions. This review will focus on three particular areas: the origins and evolution of MERS-CoV, the challenges and achievements in the development of MERS-CoV animal models, and our understanding of how novel proteins unique to MERS-CoV counter the host immune response. The origins of MERS-CoV, likely in African bats, are increasingly clear, although important questions remain about the establishment of dromedary camels as a reservoir seeding human outbreaks. Likewise, there have been important advances in the development of animal models, and both non-human primate and mouse models that seem to recapitulate human disease are now available. How MERS-CoV evades and inhibits the host innate immune response remains less clear. Although several studies have identified MERS-CoV proteins as innate immune antagonists, little of this work has been conducted using live virus under conditions of actual infection, but rather with ectopically expressed proteins. Accordingly, considerable space remains for major contributions to understanding unique ways in which MERS-CoV interacts with and modulates the host response. Collectively, these areas have seen significant advances over the last several years but continue to offer exciting opportunities for discovery.